Simplify the Proposition $$\Bigl(\bigl(P\lor Q\bigr)\land \lnot\bigr(\lnot P\land(\lnot Q\lor\lnot R)\bigl)\Bigr)\lor(\lnot P\land\lnot Q)\lor(\lnot P\land\lnot R)$$

What I've tried is simplify the $$\Bigl(\bigl(P\lor Q\bigr)\land \lnot\bigr(\lnot P\land(\lnot Q\lor\lnot R)\bigl)\Bigr) $$ First , using the Distributive law i get

$$(P\lor Q) \land\lnot\bigl((\lnot P\land\lnot Q)\lor(\lnot P\land\lnot R)\bigr)$$ Using the DeMorgan Law and Double negation law i get

$$(P\lor Q)\land(P\land Q )\land(P \lor R)$$ Using the Idempotent law i get

$$(P\lor Q)\land (P\lor R)$$

and now i'm stuck

  • $\begingroup$ Your last line simplifies to $P\lor(Q\land R)$. $\endgroup$ Oct 25, 2019 at 8:08
  • $\begingroup$ $(P \lor Q) \land (P \land Q) = P \land Q$ (2nd line from end) $\endgroup$
    – David Diaz
    Oct 25, 2019 at 9:15
  • $\begingroup$ @MichaelHoppe thanks man i got the answer $\endgroup$
    – MaxBrian
    Oct 25, 2019 at 9:18

1 Answer 1


For your last line,

Use Distributive law (backward) you get

$$P\vee(Q\wedge R)$$


You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .